Amino ether analogues of 4, 4′-dihydroxy-3-methoxy-6, 7′-cyclolignan and their activity against drug-resistant bacteria. (August 2022) - Núñez-Mojica, Guillermo; Hernández-Carrillo, Martha L.; Avalos-Alanís, Francisco G.; Garza-González, Elvira; Rivas-Galindo, Verónica M.; Silva-Mares, David A.; Bazin, Marc-Antoine; Marchand, Pascal; Camacho-Corona, María del Rayo
Abstract: Larrea tridentata antibacterial lignan 4, 4′-dihydroxy-3-methoxy-6, 7′-cyclolignan (1 ) was derivatized to obtain eleven new amino ether derivatives (2 A -12 C ). The structural elucidation of compounds was performed by analysis of 1D- and 2D NMR spectral data and HRESIMS. The antibacterial activity of compounds was determined against nine drug-resistant bacteria and two strains of Mycobacterium tuberculosis (sensitive ATCC 27294 H37Rv and drug-resistant G122). Results showed that all derivatives were devoid of activity towards six gram-negative clinical isolates assayed. However, seven derivatives displayed antibacterial activity against three gram-positive drug-resistant bacteria. Further, enhancement of antibacterial activity was only observed for the compounds 2 A and 10 C -12 C (MIC of 12.5 µg/mL) which were two-fold more active than the starting material 1 against vancomycin-resistant Enterococcus faecium . All derivatives, except compound 9 B, showed antitubercular activity against both M. tuberculosis strains. Interestingly, all the compounds, except for 2 A and 11 A, were more active than the starting material 1 (MIC of 50 µg/mL). Compound 4 C was the only compound as active as the positive control ethambutol against the drug-resistant strain M. tuberculosis G122 (MIC of 6.25 µg/mL). In addition, the derivative 7 C was the most active compound against the sensitive strain M. tuberculosis H37Rv (MIC of 6.25 µg/mL) Graphical Abstract: ga1 Highlights: Aminoether analogues of 4, 4′-dihydroxy-3-methoxy-6, 7′-cyclolignan were synthesized. The antibacterial activity of the compounds was determined. 4 C was as active as the control drug ethambutol against a multidrug resistant Mtb strain.